Management of mechanical aortic valve thrombosis during the first trimester of pregnancy. Issue 6 (16th March 2022) - Majdevac, Slavica; Susak, Stamenko; Vujic, Vanja; Okiljevic, Bogdan; Golubovic, Miodrag; Zdravkovic, Ranko
Abstract: Background: Cardiovascular diseases are the leading cause of morbidity and mortality in pregnant women. On the other hand, cardiac surgery is not so common for pregnant women. Case report: We present the case of a pregnant woman with diagnosed thrombosis of the mechanical aortic valve in the 12th gestational week. The patient underwent surgery, and successfully completed her pregnancy till the 37th gestational week. Conclusion: We showed that, despite general anaesthesia during the first trimester of pregnancy, the application of the nonpulsatile flow of extracorporeal circulation and mild hypothermia, the operation was successfully completed and that both mother and fetus survived.